Effects of Heat Treatment on The Wettability and Color Properties of Betung Bamboo (Dendrocalamus Asper) Strand. Issue 1 (September 2021) - Sipahutar, Wahyu Solafide; Maulana, Sena; Augustina, Sarah; Murda, Rio Ardiansyah; Bindar, Yazid
Abstract: Betung bamboo (Dendrocalamus Asper) has recently attracted interest as a sustainable reinforcement fiber in (polymer) composite materials. Utilization of bamboo has an advantages and disadvantages. It has a short growth cycle, lightweight, and good mechanical properties, but with poor wettability, dimensional instability, and low resistance againts biodeterioration agent. Some efforts have been devoted to alter and enhance its properties, especially wettability properties. Heat treatment under various temperature can enhance wettability properties due to chemical changes and migration of extractives, but also can induce color changes. Therefore, this study aims to investigate wettability properties and color changes of heat-treated Betung bamboo strand. The 1/3 middle of Betung bamboo was used as main material and converted into strand. Heat treatment temperatures applied were 140oC and 160oC for 3 hours. The wettability of Phenol Formaldehyde (PF) adhesive on heat treated Betung bamboo strand was measured using a sessile drop contact angle method. Constant contact angle and K-value were used as parameter of wettability. Color change of heat-treated Betung bamboo strand was measured by portable color difference meter model CDX 105 and characterized by CIE Lab. Results showed that the increasing temperature of heat treatment affected wettability and color properties. Contact angle tended to increase with an increase of temperature which is indicated an enhancement of wettability by making wood more hydrophobic. Increasing of temperature made Betung bamboo strand to be darker than that of control sample. Total color change (AE) values were 21.06 and 29.23 at 140 and 160 oC, respectively.